STATUS ANAK HASIL PERKAWINAN LIKKA SORO’ DALAM ADAT MANDAR MENURUT PERSPEKTIF KOMPILASI HUKUM ISLAM (KHI) - Ika Novitasari; Sulaeman Sulaeman; Andi Dewi Pratiwi; Widya Lestari (Program Studi Hukum Universitas Sulawesi Barat, 2023)
This study aims to analyze the status of children of Likka Soro's marriage in Adat Mandar according to the perspective of the Compilation of Islamic Law. The status of children resulting from Likka Soro' marriage in Mandar custom according to the Perspective of the Islamic Law Compilation (KHI), namely the position of a legitimate child must be based on a valid marriage according to Article 42 of the Marriage Law and Article 99 of the Compilation of Islamic Law, which states that a legitimate child is a child born from legal wedlock. Likka Soro' marriage in Mandar custom according to sharia or Islam is valid but based on Marriage Law No. 1 of 1974 Article 2 Paragraph (2) is invalid because it is not registered with the authorized agency and seen from the Compilation of Islamic Law in Article 7 the marriage of Likka Soro' has not been declared valid because it must be registered with the authorized agency to obtain a marriage book. Then in Article 6 Paragraph (2) of the Compilation of Islamic Law, it states that marriages carried out outside the supervision of a Marriage Registrar do not have legal force, therefore Likka Soro' marriages that have taken place should be registered and then recorded in civil registration to obtain a legal position. to support child survival. Factors causing the occurrence of the Likka Soro' marriage were that the woman had conceived a child out of wedlock, there was incompatibility or a desire between the woman and the man to bind themselves in a marriage relationship, there was no agreement between the families of both parties to establish kinship through marriage, men -men don't want to be responsible for the children that women have conceived because men are not sure that the child they are carrying is theirs for the reason that he is not the only one having intercourse with or having intercourse with the woman and lastly because there is promiscuity among adolescents which often causes women to pregnant out of wedlock.